Sodium-Dependent Glucose Transporter 1 (SGLT1) Stabled by HER2 Promotes Breast Cancer Cell Proliferation by Activation of the PI3K/Akt/mTOR Signaling Pathway in HER2+ Breast Cancer. (21st April 2020) - Wang, Jinlu; Ji, Hongfei; Niu, Xingjian; Yin, Lei; Wang, Yiran; Gu, Yucui; Li, Dongbo; Zhang, Han; Lu, Minghui; Zhang, Fengxia; Zhang, Qingyuan
Abstract : Aerobic glycolysis is a hallmark of tumor cells. SGLT1 plays a vital role in glucose metabolism. However, whether SGLT1 could promote cell growth and proliferation in breast cancer remains unclear. Here, we investigated the expression of SGLT1 in breast cancer and examined its role in malignant behavior and prognosis. Further, we examined the SGLT1 expression in breast cancer tissues and its relationship with clinicopathologic characteristics. We clarified that SGLT1 was overexpressed in HER2+ breast cancer cell lines and was affected by HER2 status. We further found that SGLT1 affected breast cancer cell proliferation and patient survival by mediating cell survival pathway activation. SGLT1 was overexpressed in HER2+ breast cancers and associated with lymph node metastasis and HER2+ status. Inhibition of HER2 decreased SGLT1 expression, and the extracellular acidification rate was also reduced in the UACC812 and SKBR3 cell lines. These changes could be reversed by proteasome inhibitor treatment. Knockdown of SGLT1 blocked PI3K/Akt/mTOR signaling, thereby inhibiting cell proliferation. Further, we demonstrated that high SGLT1 was significantly correlated with shorter survival in all breast cancer patients and specifically in HER2+ breast cancer patients. Therefore, we conclude that SGLT1 is overexpressed in HER2+ breast cancer, thereby promoting cell proliferation and shortening survival by activating PI3K/Akt/mTOR signaling. This study submits that SGLT1 is promising not only as a novel biomarker of HER2+ breast cancer subtype but also as a potential drug target.